Analisis Transparansi Dan Akuntabilitas Pemerintah Desa Dalam Pengelolaan Alokasi Dana Desa Di Desa Tana Toro Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Jasman Jasman; Nurjannah Nonci; Barisan Barisan (Journal of Innovative and Creativity, 2025)
This research aims to analyze the transparency and accountability of the Tana Toro Village Government in managing the Village Fund Allocation (Alokasi Dana Desa/ADD). The study is motivated by the importance of good financial governance at the village level to support sustainable rural development. The research employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the Village Head, Village Secretary, village officials, and community leaders. The results indicate that in terms of transparency, the Tana Toro Village Government has involved the community through hamlet and village deliberations and has disseminated budget information openly via public notice boards and community forums. However, challenges remain, particularly regarding the limited understanding of technical documents among the community. In terms of accountability, financial reporting and responsibilities have been carried out in accordance with regulations, using the SISKEUDES application and through regular audits by the Inspectorate. Nevertheless, administrative issues such as incomplete supporting documentation (SPJ) still need improvement. Overall, the management of ADD in Tana Toro Village reflects the principles of good governance, although further capacity building for village apparatus and enhanced community involvement are still necessary